Noninvasive Skin Autofluorescence of Advanced Glycation End Products for Detecting Ossification of the Posterior Longitudinal Ligament in the Thoracic Spine. Issue 4 (15th February 2023) - Doi, Toru; Horii, Chiaki; Tozawa, Keiichiro; Nakarai, Hiroyuki; Sasaki, Katsuyuki; Yoshida, Yuichi; Ito, Yusuke; Ohtomo, Nozomu; Sakamoto, Ryuji; Nakajima, Koji; Nagata, Kosei; Okamoto, Naoki; et al.
Abstract : Study Design: A single-center prospective observational study. Objective: The aim was to clarify the usefulness of assessing advanced glycation end products (AGEs) by noninvasive skin autofluorescence in patients with ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data: AGE accumulation is associated with various systemic disorders, including aging, diabetes mellitus, and obesity. AGEs have also been associated with OPLL, but their assessment by noninvasive skin autofluorescence has not been yet studied in these patients. Materials and Methods: We enrolled patients with degenerative spinal spondylosis and divided them into non-OPLL and OPLL groups. The OPLL group was further subdivided into cervical OPLL (C-OPLL) and thoracic OPLL (T-OPLL) groups. We compared patients' characteristics, serum laboratory data ( i.e. hemoglobin A1c, total cholesterol, creatinine, and estimated glomerular filtration rate), and the skin autofluorescence intensity of AGEs (the AGE score) between the non-OPLL and OPLL groups and among the non-OPLL, C-OPLL, T-OPLL groups. Finally, the association of the AGE score with the presence of C-OPLL or T-OPLL was assessed by multinomial logistic regression. Results: Among the 240 eligible patients, 102 were in the non-OPLL group and 138 were in the OPLL group (92 with C-OPLL and 46 with T-OPLL). We observed no significant difference in the AGE score between the non-OPLL and OPLL groups, but when comparing the score among the non-OPLL, C-OPLL, and T-OPLL groups, we found that the T-OPLL group had a significantly higher AGE score. The results of multinomial regression analysis showed that a higher AGE score was significantly associated with T-OPLL (odds ratio: 1.46; 95% CI: 1.01–2.11; P =0.044). Conclusion: The AGE score determined by noninvasive skin autofluorescence could help to screen for OPLL in the thoracic spine.